Effects of ovariectomy and resistance training on oxidative stress markers in the rat liver (Clinics, 2013)
OBJECTIVE: The objective of this study was to assess the effects of resistance training on oxidative stress markers in the livers of ovariectomized rats. METHOD: Adult Sprague-Dawley rats were divided into the following four groups (n = 8 per group): sham-operated sedentary, ovariectomized sedentary, sham-operated resistance training, and ovariectomized resistance training. During the resistance training period, the animals climbed a 1.1-m vertical ladder with weights attached to their tails; the sessions were conducted 3 times per week, with 4-9 climbs and 8-12 dynamic movements per climb. The oxidative stress was assessed by measuring the levels of reduced glutathione and oxidized glutathione, the enzymatic activity of catalase and superoxide dismutase, lipid peroxidation, vitamin E concentrations, and the gene expression of glutathione peroxidase. RESULTS: The results showed significant reductions in the reduced glutathione/oxidized glutathione ratio (4.11±0.65 nmol/g tec), vitamin E concentration (55.36±11.11 nmol/g), and gene expression of glutathione peroxidase (0.49±0.16 arbitrary units) in the livers of ovariectomized rats compared with the livers of unovariectomized animals (5.71±0.71 nmol/g tec, 100.14±10.99 nmol/g, and 1.09±0.54 arbitrary units, respectively). Moreover, resistance training for 10 weeks was not able to reduce the oxidative stress in the livers of ovariectomized rats and induced negative changes in the hepatic anti-oxidative/oxidative balance. CONCLUSION: Our findings indicate that the resistance training program used in this study was not able to attenuate the hepatic oxidative damage caused by ovariectomy and increased the hepatic oxidative stress.